2017
DOI: 10.4028/www.scientific.net/kem.727.853
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methylene Blue and Congo Red on Bentonite Modified with CaCO<sub>3</sub>

Abstract: Both bentonite and CaCO3 are cheap and abundant superior regional non-metal ores in Guangxi province, so it is very meaningful to jointly exploit bentonite and CaCO3 for real applications. In this study, bentonite modified with CaCO3 (CCB) was prepared and its adsorption performance of Congo Red (CR) and Methylene Blue (MB) was evaluated by investigating the adsorption influencing effects of initial pH, SDBS and phosphate. Adsorption isotherms and adsorption kinetics models were also fitted to analysis the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The correlation coefficient R 2 of Langmuir was 0.99, much higher than that of Freundlich isotherm, indicating better fit of experimental data with the Langmuir model. The preparation conditions and CR adsorption performance of various adsorbents were compared with the present work in Table 2 (Zhang et al, 2013;Srivastava and Sillanpää, 2016;Huang et al, 2017;Said et al, 2017;Shaba et al, 2017;Shaban et al, 2018). Compared with the traditional methods of clay adsorbents synthesis, present work can considerably shorten the reaction time.…”
Section: Adsorption Isothermsmentioning
confidence: 97%
“…The correlation coefficient R 2 of Langmuir was 0.99, much higher than that of Freundlich isotherm, indicating better fit of experimental data with the Langmuir model. The preparation conditions and CR adsorption performance of various adsorbents were compared with the present work in Table 2 (Zhang et al, 2013;Srivastava and Sillanpää, 2016;Huang et al, 2017;Said et al, 2017;Shaba et al, 2017;Shaban et al, 2018). Compared with the traditional methods of clay adsorbents synthesis, present work can considerably shorten the reaction time.…”
Section: Adsorption Isothermsmentioning
confidence: 97%
“…[23,24] On the brighter side, CaCO 3 is cheapest material found it has been used for the removal of heavy metals, [25][26][27] but mainly for dye pollutants by opting various modifications which is also very tedious and energy or materials consuming. Zhang et al [28] showed the monolayer process for mineralization of methylene blue and congo red dye with CaCO 3 modified with bentonite. Also, oxides of calcium act as low cost adsorbent [29] for toxic dyes/ organic pollutants removal in various pharmaceutical and textile industries but still needs to be explored for heavy metals elimination or decontamination of wastewater by following simpler and greener methods.…”
Section: Introductionmentioning
confidence: 99%
“…On the brighter side, CaCO 3 is cheapest material found it has been used for the removal of heavy metals, [25–27] but mainly for dye pollutants by opting various modifications which is also very tedious and energy or materials consuming. Zhang et al [28] . showed the monolayer process for mineralization of methylene blue and congo red dye with CaCO 3 modified with bentonite.…”
Section: Introductionmentioning
confidence: 99%